Coprological observations in fowl (Gallus gallus L ., 1758) naturally infested, in the region of Campo FJorido, Minas Gerais, Brazil (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1976)
A parasitological study at Campo FJorido in the State of Mitias Gerais using naturally infested chickens was performed. These were classified in three classes: cliiks, cockerels and adult chickens. The results obtained can be summarized as follows:— The adult birds showed 31.8% of negative fecal examinations fo r parasiteswhile only 3.2% of the samples from chicks were negative for endoparasites.— The percentages of infestations by Syngamus, Spirurida and Ascaridiaor Heterakis were larger in chicks than in adult chickens. On the other hand the percentage of parasitism by Capillaria, Strongyloides and Fimehandamong chicks and adult chickens were almost uniform.